Citizenship, parity of participation and the three-dimensional model analysis of Nancy Fraser - Cardoso, Fábio Luiz Lopes (Laboratório Editorial Faculdade de Ciências e Letras, 2012)
This paper seeks to portray, in a synthetic form, the theoretical elaboration of American political scientist Nancy Fraser about her threedimensional model analysis (recognition, redistribution and parity of participation) as a form of theoretical and practical intervention in the debates of recognition and shape of action of so-called new social movements. It is of key importance for his theory the elaboration of the idea of recognition and status regarding the inclusion of the political dimension in the idea of parity of participation. Both, however, have been developed during the elaboration of the theory, giving it new life, but also presenting new challenges. To make a systematic balance of this formulation is necessary to try to understand the propositions of Fraser from his latest model. We also emphasize some inroads, as the consideration of the concept of citizenship, to continue the debate on this important contribution.